AB0979 A clinical and radiographic study comparing hand involvement in idiopathic osteoarthritis and hemochromatosis arthropathy. (23rd January 2014) - Zwerina, J.; Dallos, T.; Sahinbegovic, E.; Stamm, T.; Aigner, E.; Manger, B.; Englbrecht, M.; Datz, C.; Schett, G.
Abstract : Background: Hand osteoarthritis (HOA) can result from different conditions. Most known is idiopathic HOA, but there are also secondary forms due to metabolic diseases. Hereditary hemochromatosis (HH) arthropathy is the most common form of secondary HOA. Objectives: To perform a direct comparison between idiopathic hand OA and hemochromatosis arthropathy to delineate clinical similarities and differences. Methods: In total 337 patients were assessed, 141 patients with HH arthropathy of the hands and 196 patients with primary HOA. Structured clinical assessment including hand function tests, as well as hand radiographs with scoring according to Kellgren-Lawrence, were done in all patients. Results: HH arthropathy and HOA differed significantly: Patients with HH arthropathy were younger and predominantly male as compared to HOA. In males but not females, HH arthropathy led to earlier start of symptoms than in HOA. Patients with HOA had more tender joints and worse hand function than patients with HH arthropathy, although subjective measures of joint pain and function were similar. Metacarpophalangeal and wrist joint involvement was more frequent and severe in HH arthropathy, while HOA patients had more frequently degenerative changes in the first carpometacarpal as well as proximal and distal interphalangeal joints. Conclusions: Secondary HOA in conjunction with HH and primary HOA differ significantly in terms of epidemiology, localization, severity of symptoms and radiographic changes. Disclosure of Interest: None Declared